Brain-Derived Neurotrophic Factor and Tyrosine Kinase Receptor B Involvement in Amygdala-Dependent Fear Conditioning - Rattiner, Lisa M. (J Neurosci, 2004)
Brain-derived neurotrophic factor (BDNF) and its receptor, tyrosine kinase receptor B (TrkB), play a critical role in activity-dependent synaptic plasticity and have been implicated as mediators of hippocampal-dependent learning and memory. The present study is the first to demonstrate a role for BDNF and TrkB in amygdala-dependent learning. Here, the use of Pavlovian fear conditioning as a learning model allows us to examine the concise role of BDNF in the amygdala after a single learning session and within a well understood neural circuit. Using in situ hybridization, mRNA levels of six different trophic factors [BDNF, neurotrophin (NT) 4/5, NGF, NT3, aFGF, and bFGF) were measured at varying time points during the consolidation period after fear conditioning. We found temporally specific changes only in BDNF gene expression in the basolateral amygdala after paired stimuli that supported learning but not after exposure to neutral or aversive stimuli alone. Using Western blotting, we found that the Trk receptor undergoes increased phosphorylation during this consolidation period, suggesting an activation of the receptor subsequent to BDNF release. Furthermore, disruption of neurotrophin signaling with intra-amygdala infusion of the Trk receptor antagonist K252a disrupted acquisition of fear conditioning. To address the specific role of the TrkB receptor, we created a novel lentiviral vector expressing a dominant-negative TrkB isoform (TrkB.T1), which specifically blocked TrkB activation in vitro. In vivo, TrkB.T1 lentivirus blocked fear acquisition without disrupting baseline startle or expression of fear. These data suggest that BDNF signaling through TrkB receptors in the amygdala is required for the acquisition of conditioned fear.